Tragedy, recognition, and the death of God : studies in Hegel and Nietzsche - Williams, Robert R., 1939- (Oxford : Oxford University Press, 2013)
Robert R. Williams offers a bold new account of divergences and convergences in the work of Hegel and Nietzsche. He explores four themes - the philosophy of tragedy; recognition and community; critique of Kant; and the death of God - and explicates both thinkers' critiques of traditional theology and metaphysics.
Description based on online resource; title from PDF title page (viewed on Oct. 30, 2012).
Keywords: Hegel, Georg Wilhelm Friedrich, -- 1770-1831.; Nietzsche, Friedrich Wilhelm, -- 1844-1900.; Religion -- Philosophy; Death of God